Relationship between grey scale sonographic grades of fatty liver and shear wave elastographic values: an observational study - Gupta, Neetika; Raj, Kruthik; Chandra, Ranjan; Malik, Amita; Bagri, Neha; Thakur, Manisha (International Journal of Research in Medical Sciences, 2019)
Background: Due to the growing public health menace of metabolic syndrome, the Non-Alcoholic Fatty Liver Disease (NAFLD) has been recording a burgeoning global rise. The prognosis of NAFLD is largely depends upon its histological stage. Simple steatosis has a fairer prognosis, while Non-Alcoholic Steatohepatitis (NASH) has a poorer prognosis with tendency to progression into fibrosis and end stage liver disease. Until now, the diagnosis of varying grades of NAFLD has been dependent upon liver biopsy, which is indisputably the most reliable tool to distinguish between simple steatosis, steatohepatitis, and end stage liver disease. The sonographic grading of NAFLD is primarily based on subjective findings, the results of which may vary between different observers. Hence, there is a need to identify a reliable non-invasive objective substitute. To compare the sonographic grades of fatty liver on gray scale with liver stiffness (Kpa) values of shear wave elastography. Also, an attempt to establish objective criteria for grading of fatty liver with improved accuracy and increased specificity. Methods: Cross sectional, observational study comprising of 240 adults referred for routine abdominal sonography. All patient underwent gray scale sonography and shear wave elastography and results were analysed. Results: A significant positive correlation was found between various grades of NAFLD as assessed subjectively on grey scale sonography to the liver stiffness in kilopascal (Kpa) using shear wave elastography. Conclusions: Shear wave elastography being an objective imaging tool is a reliable modality compared to grey scale sonography in diagnosis of NAFLD and has the capacity to carry out quantitative evaluation of liver parenchyma in vivo.